MS-OFFICE Untuk Meningkatkan Kinerja Karyawan Di SMA Mahapatih Mojopahit Tangerang - Arsanto Narendro; Tatang Wirawan Wisnuadji; Suwasti Broto (CV. Multi Kreasi Media, 2025)
Looking at the aspect of the ability to carry out routine administrative tasks, we have identified several factors that need improvement so that the performance of the teaching staff at SMA Mahapatih Mojopahit Tangerang can be enhanced. Administrative work in the school environment is very important to support the teaching and learning process. The management of student data and other administrative tasks directly impacts the success of education in the school. Therefore, we as partners feel it is necessary to enhance collaboration through training in software usage skills, particularly software that is commonly used in schools for managing student data and other administrative matters. We have chosen MS Office as the main focus of the training because this software is easy and practical for school staff to use. The training will begin with teaching the correct way to operate the software, followed by examples and applications in creating tables and performing simple calculations. With this training, it is expected that the skills of administrative and teaching staff will improve, allowing for better performance in the administrative aspect—which is an important element in the teaching and learning process—to be achieved more effectively and efficiently.